Analysis of epidemics of leptosphaerulina leaf spots on alfalfa and white clover in time and space - Olanya, O.M.; Campbell, C.L. (1990)
The spatial and temporal development of leaf spots on alfalfa(Medicago sativa ‘Are’ and Ladino-type white clover (Trifolium repens ‘Regal’) caused by Leptosphaerulina trifolii were mentioned during spring 1987, fall 1987, and spring 1988. In spring 1987, diseases gradients developed from diseased alfalfa to both white clover, little diseases developed on either host in plot with diseases clover at the focus. In fall 1987 and spring 1988, disease developed from alfalfa or clover on both hosts. Generally, diseases increased more rapidly when alfalfa was the recipient host than when clover was, regardless of the host at the disease focus. Area under the disease progress curve (temporal) and volume under the disease progress curve (temporal and spatial) were greater when alfalfa was the recipient host than when clover was the recipient host